KEKAYAAN INTELEKTUAL DI UNIVERSITAS: SEBUAH STUDI DESKRIPTIF - Yustina, Andi Ina (JURNAL AKUNTANSI DAN AUDITING, 2015)
This paper briefly discusses about intellectual capital in university. Intellectual capital is intangible asset that is likely to be more difficult to evaluated because it can not be quantified objectively (non-financial objective).Intellectual capital consist of three dimension: human capital, organization capital, and social capital. Each of this dimension have several indicators that can be used by university in calculating all the intellectual capital. This paper is important to describe all the indicators of intellectual capitalin order to provide value-added outcomes for all parties, either internal and external university. Clear indicator and proper in reporting intellectual capital, university will show the good performance of its human resources.